Identifikasi Batuan Granit Daerah Prospek Panas Bumi Nyelanding menggunakan Metode Magnetik - Ahmat Munawir Siregar; Ira Kusuma Dewi; Ngatijo Ngatijo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aimed to identify granite rocks around the Nyelanding geothermal area, especially in the geothermal manifestations. This research used the magnetic method to analyze the subsurface structure of the geothermal area. Correction of magnetic data was performed in Microsoft excel 2010 software and two-dimensional modeling was performed using Oasis Montaj 8.4. The results showed that there are three layers of rock under Nyelanding hot springs, namely granite with a susceptibility of 0.009 - 0.05 SI to a depth of 500 meters and a layer of sandstone - clay, as well as layers of clay, gravel and silt with a susceptibility of 0.00001 - 0, 00005 SI. In conclusion, the local geology of the Nyelanding hot spring area is dominated by the presence of granite to a depth of 500 meters. The results of forward modeling on layers A-A' and C-C' show the subsurface structure of Nyelanding hot springs in the form of a granite rock basin which is estimated to be able to accumulate geothermal energy. Key words: Nonvolcanic Geothermal, Magnetic Method, Granite Susceptibility, Forward Modeling